1968
DOI: 10.1002/dev.420010410
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit eyelid conditioning: Effects of age, interstimulus interval, and intertrial interval

Abstract: (1969). Rabbit Eyelid Conditioning: Eoects of Age, InterstimuZus Interval, and Inlertrial Interval. DEVELOPMENTAL PSYCHOBIOLOGY, l(4): 276-279. Young rabbits (5-7 weeks old) conditioned more rapidly and demonstrated longer latency responses than older rabbits (14-20 weeks old) with an 800-msec interstimulus interval. With a 200-or 400-rnsec interval, conditioning rate and response latency were similar for both age groups. Although a 4-min intertrial interval produced conditioning in fewer trials than a 1-min i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1969
1969
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…For instance, in the present experiments, there were fewer nonreinforced presentations of the facilitator per session, and they were more widely spaced, with a mean ITI of 150 sec, than in Rescorla's (1986a) study, in which a more concentrated exposure with a mean ITI of 60 sec was used. Other studies have shown that the acquisition of Pavlovian conditioning may be improved with longer ITIs (Frey & Ross, 1968;Gibbon, Baldock, Locurto, Gold, & Terrace, 1977;Kehoe & Gormezano, 1974) and fewer trials per day (Kehoe & Gormezano, 1974). Similar benefits of trial spacing have been documented for the acquisition of serial feature-positive discriminations (Holland, 1995(Holland, , 1999.…”
Section: Discussionmentioning
confidence: 60%
“…For instance, in the present experiments, there were fewer nonreinforced presentations of the facilitator per session, and they were more widely spaced, with a mean ITI of 150 sec, than in Rescorla's (1986a) study, in which a more concentrated exposure with a mean ITI of 60 sec was used. Other studies have shown that the acquisition of Pavlovian conditioning may be improved with longer ITIs (Frey & Ross, 1968;Gibbon, Baldock, Locurto, Gold, & Terrace, 1977;Kehoe & Gormezano, 1974) and fewer trials per day (Kehoe & Gormezano, 1974). Similar benefits of trial spacing have been documented for the acquisition of serial feature-positive discriminations (Holland, 1995(Holland, , 1999.…”
Section: Discussionmentioning
confidence: 60%
“…Possibly, the use of a .25•sec interstimulus interval in the hippocampal study and our use of .6 sec is the most important difference. Frey (1969) has shown that interstirnulus intervals of .4 sec produce better acquisition than do those of .6 sec, and performance improves further down to .2 sec (Frey & Ross, 1969). Another important change in the present study was to measure the eyelid response rather than the nictitating membrane.…”
Section: Discussionmentioning
confidence: 88%
“…The functional importance of the differences between schizophrenia patients and normal subjects at the interstimulus interval of 500 ms may relate to studies of animal and human learning. In animals, conditioning of skeletal muscle reflexes is maximal when the conditioned and unconditioned stimuli are separated by 500 ms (Frey and Ross 1968). Verbal learning in humans is also optimum when stimuli are approximately 500 ms apart (Conrad 1957).…”
Section: A7-nicotinic Receptor and The Neurobiology Of Psychosismentioning
confidence: 99%